أهمية الإبداع التكنولوجي كمصدر للميزة التنافسية في المؤسسات الصناعية - غقال, الياس; مدوكي, يوسف; زقرير, عادل (جامعة الوادي - University of Eloued, 2017)
يعتبر الإبداع التكنولوجي الركيزة الأساسية التي تعتمد عليها المؤسسات الاقتصادية لمواجهة تحديات العصر، فجميع المؤسسات الصناعية في الوقت الحالي معنية كثيرا بالإبداع التكنولوجي، خاصة مع التطورات المذهلة للاكتشافات العلمية وانتشار المعرفة، وكذلك اشتداد المنافسة في المجال الصناعي، كما لا ننسى التعقيد والتوجهات الحديثة التي تتميز بها المجتمعات، حيث أصبح من الضروري إنتاج سلع حديثة ومتطورة أو طرق جديدة للتصنيع تلبي حاجات ورغبات المستهلكين التي تتطلع إلى الأحسن وكذلك تزيد من إنتاجية المؤسسة، وذلك بالاهتمام بعمليات البحث والتطوير بشكل كبير، وهذا من أجل اكتساب ميزة تنافسية تضمن لها البقاء والاستمرار في مثل هذا المحيط الصعب. إن المؤسسات الصناعية ككيان اقتصادي واجتماعي- وفي ظل هذه التطورات- وجب عليها من أجل ضمان بقائها واستمراريتها أن ترفع هذا التحدي وتدعم إستراتيجيتها التنافسية بالاهتمام وبتسيير واستغلال مختلف مواردها المادية والبشرية وذلك من أجل التطوير والإبداع في المجال التكنولوجي. انطلاقا مما سبق وجدنا أنفسنا مهتمين بموضوع الإبداع التكنولوجيقصد الوصول إلى معرفة كيف يساهم هذا الأخير في اكساب المؤسسات الصناعية لمزايا تنافسية، وبالتاليالتعزيز من تنافسيتها في ظل محيطها التنافسي المعقد. Technological innovation is the cornerstone on which depend economic institutionsto meetingera challenges. All industrial firms are, currently, concerned with technological innovation.Especially, with the amazing developments of scientific discoveries, the intensification of competition in the industrial field, as well as the complexity recent trends that characterize it.Therefore, it is necessary to produce new and sophisticated products or processes that meet the consumer’s needs and desires,and increase the firm’s productivity, by taking a keen interest in research and development, In order to gain a competitive advantage that ensures its survival and continuity in such a difficult environment.For that, firms must raise this challenge and support their competitive strategy by managing and exploiting their various resources in order to develop and innovate in the technological field. Proceeding from the above. Our research papers included the subject of technological innovation in order to reveal how, this lattre, contributes to the acquisition of competitive advantages, and thus, to enhance the competitiveness of industrial firms in their complex competitive environment.
The importance of technological innovation as a source of competitive advantage in industrial establishments
مقال
Keywords: الإبداع، الإبداع التكنولوجي، الميزة التنافسية، التميز بالتكلفة الأقل، تميز المنتج; Innovation, technological innovation, competitive advantage, excellence at lower cost, product differentiation